2022
DOI: 10.1097/mat.0000000000001653
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Life Support Organization Guideline for Transport and Retrieval of Adult and Pediatric Patients with ECMO Support

Abstract: Disclaimer: This guideline for the preparation for and undertaking of transport and retrieval of patients on extracorporeal membrane oxygenation (ECMO) is intended for educational use to build the knowledge of physicians and other health professionals in assessing the conditions and managing the treatment of patients undergoing ECLS / ECMO and describe what are believed to be useful and safe practice for extracorporeal life support (ECLS, ECMO) but these are not necessarily consensus recommendations. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…A total of 63 different mobile ECMO team members were exposed to COVID-19 patients in a total of 199 episodes of Current guidelines also recommend a hub-and-spoke model to better utilize resources and centrcentralizealise this highly demanding service. 22 The risk of transmission of COVID-19 infection to HCWs cannot be underestimated. Globally, nearly 4% of patients reported to be infected with COVID-19 were HCWs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 63 different mobile ECMO team members were exposed to COVID-19 patients in a total of 199 episodes of Current guidelines also recommend a hub-and-spoke model to better utilize resources and centrcentralizealise this highly demanding service. 22 The risk of transmission of COVID-19 infection to HCWs cannot be underestimated. Globally, nearly 4% of patients reported to be infected with COVID-19 were HCWs.…”
Section: Resultsmentioning
confidence: 99%
“…Current guidelines also recommend a hub‐and‐spoke model to better utilize resources and centrcentralizealise this highly demanding service. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of extracorporeal membrane oxygenation (ECMO) in Coronavirus 2019 (COVID-19) associated severe acute respiratory distress syndrome (ARDS) has been a subject of debate because of the early negative results [76,77]. Despite that ECMO has been recommended as supportive intervention by multiple societies [78,79]. However, subsequent studies from the extracorporeal life support organization (ELSO) showed that the use of V-V ECMO in COVID-19 is associated with an in-hospital mortality of 36.9-51.9% at 90 days [80,81].…”
Section: Extracorporeal Membrane Oxygenation During Coronavirus 2019 ...mentioning
confidence: 99%
“…Clear, closed loop communication is an important aspect throughout. The best method to train the transport team is by conducting simulation scenarios to address the most common complications that could arise [78]. ECMO centers are highly encouraged to develop ECMO transport checklists aimed at minimizing the near misses and reduce human-factor error.…”
Section: Transportation Of Patients On Extracorporeal Membrane Oxygen...mentioning
confidence: 99%